Beyond metals: theoretical discovery of semiconducting MAX phases and their potential application in thermoelectrics - Khazaei, Mohammad; Maleki, Iraj; Koshi, Namitha Anna; Ranjbar, Ahmad; Miao, Nanxi; Wang, Junjie; Khaledialidusti, Rasoul; Kuehne, Thomas D.; Lee, Seung-Cheol; Bhattacharjee, Satadeep; Hosano, Hamid; Allaei, S. Mehdi Vaez; et al. (Royal Society of Chemistry, 2024)
MAX phase is a family of ceramic compounds, typically known for their metallic properties. However, we show here that some of them may be narrow bandgap semiconductors. Using a series of first-principles calculations, we have investigated the electronic structures of 861 dynamically stable MAX phases. Notably, Sc2SC, Y2SC, Y2SeC, Sc3AuC2, and Y3AuC2 have been identified as semiconductors with band gaps ranging from 0.2 to 0.5 eV. Furthermore, we have assessed the thermodynamic stability of these systems by generating ternary phase diagrams utilizing evolutionary algorithm techniques. Their dynamic stabilities are confirmed by phonon calculations. Additionally, we have explored the potential thermoelectric efficiencies of these materials by combining Boltzmann transport theory with first-principles calculations. The relaxation times are estimated using scattering theory. The zT coefficients for the aforementioned systems fall within the range of 0.5 to 2.5 at temperatures spanning from 300 to 700 K, indicating their suitability for high-temperature thermoelectric applications. Some MAX phase can be narrowband semiconductor with superior thermoelectric performance.